'The weather is like the game we play': Coping and adaptation strategies for extreme weather events among ethnic minority groups in upland northern Vietnam. (11th October 2016) - Delisle, Sarah; Turner, Sarah
Abstract: The Vietnamese government, along with country‐based non‐government organisations, are well aware of the vulnerability of Vietnam's coastal and low‐lying areas to extreme weather events. Yet scant attention has been paid to extreme weather hazards affecting Vietnam's northern mountainous regions and the livelihoods of ethnic minority farmers residing there. Building on conceptual tools from vulnerability, food security and sustainable livelihoods literatures, we examine the impacts of extreme weather, namely drought and severe cold spells, in Vietnam's northern uplands. We explore the degree to which these events impact the livelihood portfolios and food security of ethnic minority farmers, and examine the coping strategies households initiate, based on their ecological knowledge as well as recent market integration initiatives. Drawing on ethnographic fieldwork with ethnic minority Hmong and Yao semi‐subsistence households undertaken yearly from 2012 to 2014, we demonstrate that financial capital – now more central to households' livelihoods than ever before due to state‐sponsored agricultural intensification – is an important means for farmers to cope with extreme weather events. Yet concurrently, longstanding culturally rooted social capital, networks and ties remain critical. Nonetheless, short‐ and long‐term adaptation is not widespread, leading us to investigate possible explanations.